Social Reintegration after the Implementation of Restorative Justice in the Indonesian Criminal Code - Amarini, Indriati; Samhudi, Gamalel Rifqi; Mukarromah, Safitri; Ismail, Noorfajri; Saefudin, Yusuf (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
The current criminal code has been in force in Indonesia since 1918. Indonesia formulated criminal law reform in 1963 and in 2023, a law on the national criminal code was issued. The spirit of the Indonesian criminal code is reformative, progressive, and responsive to changes to the law. One of the strengths of criminal law is regulating criminal law from the perspective and achievement of justice to repair and restore the situation after the event and judicial process known as restorative justice. The desire to strengthen restorative justice programs takes a long time and is complicated. This research aims to analyze the development of the concept of social reintegration through the application of restorative justice in the criminal justice process. This research was conducted qualitatively using secondary data and doctrinal legal study methods. The results showed that changes in criminal law arrangements caused opinion differences since restorative programs are widely used as a substitute for traditional and retributive approaches. The application of restorative justice in national criminal law must be implemented. Social reintegration in the implementation of restorative justice as regulated in the Criminal Code can be successful through commitment and collaboration between the community, government and law enforcement officials